A new species of the genus Mongoloniscus Verhoeff, 1930 (Crustacea: Isopoda: Agnaridae) from China - Yang, Lina; An, Jianmei (Zootaxa, 2021)
A new species of suborder Oniscidea from northeast China, Mongoloniscus chevronus sp. nov., is described and illustrated. The new species is most related to M. sinensis, only can be distinguished from the latter and other congeners by all pereonites with concave-convex-concave posterior margins, pleon without any decorations. But it can be found new to science by Cox1 gene. A key to all species of genus Mongoloniscus is presented herein.